Prinsip Kerja Sama Grice pada Animasi Bahasa Mandarin Xiong Xiong Le Yuan 3 - Handayani, Siti (Fenghuang: Jurnal Pendidikan Bahasa Mandarin, 2023)
Language is an important communication tool in daily interactions. Language in communication must be used as well as possible. The success of using language in the process of communication is not only by choosing good diction, but also needs to be aligned with the context of communication (pragmatics). Cooperative principles is one of the principles of communication in pragmatics. Grice's cooperativeprinciple in term of creating an effective communication is categorized into four principles, namely: (1) the principle of quantity; (2) the principle of quality; (3) the principle of relevance; and (4) the principle of implementation. The purpose of this study is to describe the fulfillment of Grice's cooperative principle in the conversation of the Chinese animation film xiong xiong le yuan 3. The research method used is qualitative descriptive. The results of the study shows that there is fulfillment of Grice's cooperative principle in the animation film xiong xiong le yuan 3. Fulfillment is carried out by applying Grice's cooperative principle in every communication made by speakers and speech partners. The application of the principle of good cooperation in an animated film can also produce a good impact in conveying the messages contained in an animated film to the audience.